Dibenzo[a, e]Cyclooctatetraene‐Functionalized Polymers as Potential Battery Electrode Materials. Issue 18 (3rd March 2021) - Desmaizieres, Gauthier; Speer, Martin E.; Thiede, Inna; Gaiser, Philipp; Perner, Verena; Kolek, Martin; Bieker, Peter; Winter, Martin; Esser, Birgit
Abstract: Organic redox polymers are attractive electrode materials for more sustainable rechargeable batteries. To obtain full‐organic cells with high operating voltages, redox polymers with low potentials (<2 V versus Li|Li + ) are required for the negative electrode. Dibenzo[ a, e ]cyclooctatetraene (DBCOT) is a promising redox‐active group in this respect, since it can be reversibly reduced in a two‐electron process at potentials below 1 V versus Li|Li + . Upon reduction, its conformation changes from tub‐shaped to planar, rendering DBCOT‐based polymers also of interest to molecular actuators. Here, the syntheses of three aliphatic DBCOT‐polymers and their electrochemical properties are presented. For this, a viable three‐step synthetic route to 2‐bromo‐functionalized DBCOT as polymer precursor is developed. Cyclic voltammetry (CV) measurements in solution and of thin films of the DBCOT‐polymers demonstrate their potential as battery electrode materials. Half‐cell measurements in batteries show pseudo capacitive behavior with Faradaic contributions, which demonstrate that electrode composition and fabrication will play an important role in the future to release the full redox activity of the DBCOT polymers. Abstract : Redox polymers with dibenzo[ a, e ]cyclooctatetraene (DBCOT) side groups are synthesized from monofunctionalized DBCOT derivatives. They feature two‐electron reductions at low voltages with higher reversibility compared to COT, which makes them attractive as negative electrode materials for rechargeable dual‐ion batteries.